McGraw-Hill's GMAT : - Hasik, James (McGraw-Hill, 2007)
To compete for admission to a top business school in the United States, students must score in the high 600s. Conforming to the new GMAT first being administered in 2006, McGraw-Hill's GMAT is specifically written to help you achieve this crucial score or better without breaking a sweat. Filled with examples and review material geared to college-level study, this guide emphasizes the quantitative section of the exam, widely recognized as the best predictor of future performance in the business school curriculum.